2016
DOI: 10.3895/rbta.v10n2.3261
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Da Cinética De Secagem De Polpa De Carambola

Abstract: O processo de secagem de produtos agrícolas tem sido uma técnica muito empregada para redução do teor de água dos produtos com o intuito de dificultar o crescimento microbiano e a ocorrência de reações químicas e bioquímicas, possibilitando o armazenamento seguro por longos períodos, bem como reduzir a massa e volume a ser transportado. O presente trabalho teve por objetivo realizar um estudo da cinética de secagem de polpa de carambola (Averrhoa carambola) para as temperaturas de 40, 50 e 60 °C e 1,0 m/s de v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…This corroborates the results obtained by Gouveia et al (2003) in studies with the drying curve of cajá, because temperature is one of the factors of greatest influence in the drying process, and the higher the temperature, the shorter the drying time and, consequently, the faster the equilibrium moisture content (ME) of the product is reached. Similar results were found by Pena and Mendonça (2009) in the drying processes of passion fruit residual fiber, by Borges et al (2008), with the drying kinetics of pumpkin slices and Silva et al (2016) with star fruit pulp.…”
Section: Discussion Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…This corroborates the results obtained by Gouveia et al (2003) in studies with the drying curve of cajá, because temperature is one of the factors of greatest influence in the drying process, and the higher the temperature, the shorter the drying time and, consequently, the faster the equilibrium moisture content (ME) of the product is reached. Similar results were found by Pena and Mendonça (2009) in the drying processes of passion fruit residual fiber, by Borges et al (2008), with the drying kinetics of pumpkin slices and Silva et al (2016) with star fruit pulp.…”
Section: Discussion Resultssupporting
confidence: 82%
“…Based on the parameter k 0 estimates presented in Table 2, it was observed that the values obtained were close to 1 at both temperatures, as expected, since they refer to 100% of the initial moisture content of jabuticaba pulp, as described by Nunes et al (2014). Silva et al (2016) studied the drying of star fruit pulp and values close to 1 for k 0 when adjusting the Henderson model. Considering the parameterization of the WS model at the beginning of the process at n = 1 (time zero seconds), the model presents moisture ratio equal to 1, as estimated by nonlinear models, and the model T has no explicit relation with values.…”
Section: Discussion Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fruits in particular, due to the high moisture content, are very susceptible to deterioration by the action of microorganisms. Thus, the utilization of drying has been increasingly widespread because, in addition to offering a good quality product, this process allows longer storage and shelf life (Silva et al, 2016).…”
mentioning
confidence: 99%